Resource management for meteorological service in cloud‐edge computing: A survey. Issue 6 (7th January 2020) - Tang, Hongsheng; Zhang, Xing; Fu, Shucun; Liu, Xihua; Wu, Qi; Qi, Lianyong
Abstract: The ever‐increasing volume of data and the higher demand for real‐time services in the meteorological industry have made the relevant departments face some problems such as how to process data efficiently and deliver services instantly. Hence, by intervening in cloud computing and building meteorological cloud platform, the data are effectively managed and processed which means reliable services could be satisfied. However, a large amount of complex heterogeneous data generated by meteorological stations remote from the cloud center is sent to the cloud for processing to impose bandwidth pressure on the cloud. It will bring substantial access delays in case of frequent access. Meanwhile, the data in the public cloud will encounter security problems for the sensitivity. Therefore, appropriate assistive techniques such as edge computing are urgent to be chosen to solve the aforementioned problems. The collaborative work of edge computing and cloud makes meteorological data sent to the edge nodes for processing, which effectively cuts down the bandwidth pressure, reduces the transmission delay, and advances data security of the cloud. In this paper, we first describe the architecture, classification, and definition of meteorological services in the cloud. Then, the resource management of meteorological services in edge computing and cloud computing is summarized respectively. Furthermore, meteorological applications in cloud computing is introduced. Besides, we explore the future work of meteorological service provisioning in collaborative edge computing and cloud. Abstract : (1) The architecture, classification, and definition of meteorological services in the cloud has been described in this paper. (2) The resource management of meteorological services in edge computing and cloud computing are summarized respectively in this paper. (3) The meteorological applications in cloud computing are introduced and the future work of meteorological service provisioning in collaborative edge and cloud computing is explored in this paper.